Evaluation of Surgical Freedom for One-and-a-Half Nostril, Mononostril, and Binostril Endoscopic Endonasal Transsphenoidal Approaches - Yang, Jin; Wen, Guodao; Tang, Chao; Zhong, Chunyu; Zhu, Junhao; Cong, Zixiang; Ma, Chiyuan (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective This article determines which of the one-and-a-half nostril, mononostril, and binostril endoscopic endonasal transsphenoidal approaches provide a superior manipulation during surgery.Methods The three approaches were orderly performed on 10 silicon-injected cadaveric heads to quantitatively assess surgical freedom and attack angle for sella. Measurements were determined with a standardized method under neuronavigation system using data of computed tomography.Results The one-and-a-half nostril endoscopic transsphenoidal approach (OETA) offered superior exposed area than that of the mononostril approach (META), and similar to that of the binostril approach (BETA). For surgical freedom at anatomic targets, the OETA showed greater surgical flexibility at pituitary center, the right medial optic carotid recess (R-mOCR), the left mOCR, the medial intersection of the right cavernous internal carotid artery, and extension line of upper margin of the clivus (R-mICC) than those of the META, and similar to those of the BETA.For sagittal angle of attack to the R-mOCR, R-mICC, and L-mOCR, the OETA can provide better angular freedom for surgeon than that of the META, and similar to that of the BETA. The OETA had the same axial attack to the pituitary center with the BETA. The OETA and the META had limited surgical freedom at L-mICC, and both inferior to the BETA.Conclusion The OETA has similar exposed area, surgical freedom, and attack angle for most anatomic targets to the BETA without resecting contralateral nasal septal mucosa, and obviously superior to the META.
Keywords: one-and-a-half-nostril; endoscopic surgery; endonasal trans-sphenoidal approach; cadaver study; pituitary adenomas; manipulation space; surgical freedom